Numerical Simulation of Thermal Cycling and Vibration Effects on Solder Layer Reliability in High-Power Diode Lasers for Space Applications - Lei Cheng; Huaqing Sun; Xuanjun Dai; Bingxing Wei (Micromachines)
High-power laser diodes (HPLDs) are increasingly used in space applications, yet solder layer (SL) reliability critically limits their performance and lifespan. This study employs finite element analysis to evaluate SL failure mechanisms in microchannel-cooled HPLDs with two packaging configurations under thermal cycling and vibration. Based on the Anand constitutive model, contour plot analysis revealed that the critical stress–strain regions in both SLs were located at their edges. The stress–strain values along the X-axis of the SLs exceeded those in other axial directions, and SL failure would preferentially initiate from the edges along the cavity length direction. During random vibration analysis with excitation applied along the Z-axis, the equivalent stresses in both SLs exceeded X-/Y-axis levels. However, these values remained far below their yield strengths, indicating that only elastic strain and high-cycle fatigue occurred in the SLs. The calculated thermal fatigue lives of the two SLs were 2851 cycles and 5730 cycles, respectively. Their random vibration fatigue lives were determined as 5.75 × 107 h and 8.31 × 107 h. Using damage superposition under combined thermal-vibration loading, the total fatigue lives were predicted as 14,821 h and 29,786 h, respectively, with thermal cycling-induced damage dominating the failure mechanism.